Sudden bilateral deafness from hyperleukocytosis in chronic myeloid leukemia - Resende, Lucilene Silva Ruiz e [UNESP]; Coradazzi, A. L. [UNESP]; Rocha, C. [UNESP]; Zanini, J. M. [UNESP]; Niéro-Melo, L. [UNESP] (Karger Publishers, 2000)
Sudden-onset bilateral deafness as a clinical manifestation of hyperleukocytosis in chronic myeloid leukemia (CML) is a rare occurrence. We found only 27 clinical descriptions in 16 published papers. In this work, the authors present a review on deafness in CML and describe a new case with prominent hyperleukocytosis, where the neurological findings suggest slowing of the circulation through small blood vessels in the brainstem as the cause of deafness. The evolution was good after treatment. To our knowledge, this is the second case documented with electrical auditory brainstem-evoked potentials and the first with magnetic resonance imaging. Copyright (C) 2000 S. Karger AG, Basel.
Keywords: Chronic myeloid leukemia; Deafness; Hyperleukocytosis; adult; auditory system; brain circulation; brain stem; capillary flow; case report; chronic myeloid leukemia; clinical feature; evoked brain stem response; female; hearing loss; human; leukocytosis; neurologic examination; nuclear magnetic resonance imaging; pathogenesis; priority journal; Basilar Artery; Blood Flow Velocity; Blood Viscosity; Brain Stem; Ear, Inner; Female; Hemorrhage; Humans; Leukemia, Myeloid, Chronic; Leukocytosis; Magnetic Resonance Imaging; Male; Microcirculation; Middle Aged